Pengembangan Model Pembelajaran Berbasis Inkuiri-Transaksional untuk Pendidikan Agama Islam Aspek Sejarah pada Sekolah Menengah Kejuruan - Khoirawati - (JTP - Jurnal Teknologi Pendidikan, 2014)
The purpose of this study was to develop an instructional materials model of the world history of Islam religion for Vocational High School. This study employed a research and development method. The instructional materials developed based on inquiry-trans- actional approach, The eld research was conducted at SMK Pagar Alam City-South Su- matra province, involving of 11 experts, 53 Vocational High School students, 3 Vocational High School teachers and, 2 educational of cers. The results of the study were: (1) a con- ceptual model of instruction of the world history of Islam religion; (2) a procedural model of instructional design for developing instructional materials; (3) a set of instructional materials model of the world history of Islam religion, consisted of printed, interactive Compact Disc (CD), teachers guide, and teaching aids.